A review of the essential visual skills required for soccer: Beyond 20–20 optometry - Millard, Lourens; Breukelman, Gerrit Jan; Mathe, Nonkululeko; Shaw, Ina; Shaw, Brandon S. (Frontiers in Sports and Active Living, 2022)
In ball sports such as soccer, the visual system is critical in guiding a player’s search for crucial information that underpins skilful behavior, which requires the incorporation of all the relevant information in the environment in order to make successful decisions under pressure. However, vision in sport, and focusing on the specific visual skills required to be successful in a particular sport has largely been a practice ignored by experts and coaches as being an essential component of athletic performance. This is the first attempt to summarize and compile the necessary visual skills for soccer. This review’s evidence suggests that, while current research still tends to focus on visual skills as a whole, there is a need to streamline this focus to the necessities of a particular sport. Furthermore, in identifying the visual skills essential for soccer, it allows for the effective training and testing of these skills, as well as for talent identification.